Front Metter SOCA January Vol 15, No 1, 2021 - Front Metter SOCA January Vol 15, No 1, (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2021)
Front Metter SOCA January Vol 15, No 1, 2021